Investment and Insider Trading - Bernhardt, Dan; Hollifield, Burton; Hughson, Eric (Review of Financial Studies, 1995)
We study insider trading in a dynamic setting. Rational, but uninformed, traders choose between investment projects with different levels of insider trading. Insider trading distorts investment toward assets with less private information. However, when investment is sufficiently information elastic, insider trading can be welfare-enhancing because of more informative prices. When insiders repeatedly receive information, they trade to reveal it when investment is information elastic because good news increases investment and hence future insider profits. Thus, more information is revealed and uninformed agents are exploited less frequently by insiders. Both effects are Pareto-improving. Finally, we consider various insider-trading regulations.